Wing morphological changes in Drosophila melanogaster exposed to Bisphenol-A and Acrylamide - SITI ZUBAIDAH; AHMAD FAUZI; DENY SETIAWAN; YAYUK MULYATI; NINDIANA CHOIRUNISA’; NATASYA ADIBA ZAHRAH (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Zubaidah S, Fauzi A, Setiawan D, Mulyati Y, Choirunisa’ N, Zahrah NA. 2025. Wing morphological changes in Drosophila melanogaster exposed to Bisphenol-A and Acrylamide. Biodiversitas 26: 4567-4576. Bisphenol-A (BPA) and acrylamide are two contaminants commonly found in processed food and beverage products. This study aimed to evaluate the impact of acute exposure to BPA and acrylamide contaminants on changes in Drosophila melanogaster wing morphology. The use of wings is based on their sensitivity to environmental changes and is one of the important organs for locomotion and mating in flies. In this study, the wild-type, black, and white strains of D. melanogaster were cultured for two generations to observe the acute exposure to these two contaminants. The statistical analysis showed that acute exposure to BPA and acrylamide for two generations did not correlate strongly with wing length and width changes in the population of the three D. melanogaster strains (p<0.01). We suspect that the lack of correlation may be influenced by the non-monotonic nature of BPA, the detoxification pathway of acrylamide, and exposure studies that are still limited to acute exposure. Of all flies observed, no wing morphological changes were found in the control group. However, <15% of the group exposed to BPA and acrylamide showed wing deformities (e.g., curled, wrinkled, and notched, broken wing veins, detachment, failure in growth, and imperfections in the formation of wing edges or wing cells). The results of this study require further studies, especially on other aspects of the study and exposure over several generations, long enough to see the impact of chronic exposure to BPA and acrylamide over the next few generations.